In Vivo Blockade of Murine ARTC2.2 During Cell Preparation Preserves the Vitality and Function of Liver Tissue-Resident Memory T Cells - Rissiek, Björn; Lukowiak, Marco; Raczkowski, Friederike; Magnus, Tim; Mittrücker, Hans-Willi; Koch-Nolte, Friedrich (Frontiers in Immunology, 2018)
On murine T cells, GPI-anchored ADP-ribosyltransferase 2.2 (ARTC2.2) ADP-ribosylates the P2X7 ion channel at arginine 125 in response to nicotinamide adenine dinucleotide (NAD+) released during cell preparation. We have previously shown that chronic gating of P2X7 by ADP-ribosylation reduces the vitality and function of regulatory T cells and natural killer T cells that co-express high levels of ARTC2.2 and P2X7. Here, we evaluated the expression of ARTC2.2 and P2X7 by effector and memory T cells in the liver of naïve mice and after infection with Listeria monocytogenes (Lm). We found that KLRG1−/CD69+ tissue-resident memory T cells (Trm) in the liver of naïve mice and 7 weeks after infection with Lm express high levels of ARTC2.2 and P2X7. Isolation of liver Trm and subsequent incubation at 37°C resulted in cell death of the majority of CD4+ and CD8+ Trm. Injection of the ARTC2.2-blocking nanobody s+16a 30 min prior to organ harvesting effectively prevented ADP-ribosylation of P2X7 during cell preparation and thereby prevented NAD-induced cell death of the isolated Trm upon subsequent incubation at 37°C. Consequently, preserving Trm vitality by s+16a injection enabled a highly sensitive in vitro cytokine expression profile analyses of FACS sorted liver Trm. We conclude that in vivo blockade of ARTC2.2 during cell preparation by nanobody s+16a injection represents a valuable strategy to study the role and function of liver Trm in mice.